Ask a New Question
Search
Use the Associative Property to determine which expressions are equivalent.(1
Use the associative property to determine which expressions are equivalent
A: -3*(4x*-2)*-6y=(-3*4x)*-2*-6y B:
1 answer
asked by
hanjisung
26 views
Use the Associative Property to determine which expressions are equivalent.
−3⋅(4x⋅−2)⋅−6y=−7xy
1 answer
13 views
Use the Associative Property to determine which expressions are equivalent..
A. -3*(4x*-2)*-6y=18-8x B. -3*(4x*-2)*-6y=-7xy C.
1 answer
17 views
Use the Associative Property to determine which expressions are equivalent.
A. -3*(4x*-2)*-6y=18-8x B. -3*(4x*-2)*-6y=-7xy C.
1 answer
19 views
Use the Associative Property to determine which expressions are equivalent.
−3⋅(4x⋅−2)⋅−6y=18−8x
1 answer
25 views
Use the Associative Property to determine which expressions are equivalent.
−3⋅(4x⋅−2)⋅−6y=18−8x
1 answer
25 views
Use the Associative Property to determine which expressions are equivalent. (1 point)
0 - 3. (4x • - 2) • - 6y = 18 - 8x 0 -3
1 answer
5 views
Use the Associative Property to determine which expressions are equivalent point) - 3 - (4x + 2) * (- 6)g = 18 - 8z; - 3 - (4x +
1 answer
13 views
Use the Associative Property to determine which expressions are equivalent.(1 point)
−3⋅(4x⋅−2)⋅−6y=(−3⋅4x)(−2�
1 answer
asked by
Finally Some Answers
11 views
Use the Associative Property to determine which expressions are equivalent. (1 point)
0 - 3. (4x • - 2) • - 6y = 18 - 8x 0 -3
1 answer
5 views